Implementasi Sudut Baca dalam Meningkatkan Minat Baca Siswa SDN 1 Banteng Putih - Maftuhah, Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2024)
This research aims to determine the implementation of the reading perspective in enhancing the reading interest of fifth-grade students at State Elementary School 1 Bantengputih Karanggeneng Lamongan. This research is a qualitative descriptive study with data sources from interviews, observations, and documentation. The data obtained is then analyzed to provide an overview of the implementation of the reading corner in enhancing the reading interest of fifth-grade students at State Elementary School 1 Bantengputih. The research results indicate an increase in reading interest after establishing a reading corner in the classroom. To support this, getting students into the habit of reading for 10-15 minutes before learning activities begin is also quite effective in increasing students' interest in reading. In addition, the utilization of free periods or the replacement of class time with reading in the reading corner also serves as evidence of the implementation of the reading corner in the 5th grade of State Elementary School 1 Bantengputih.